PERANCANGAN VISUAL BRANDING RIRIEZ KARAOKE KOTA MUKOMUKO BENGKULU - Eggi Chaprisimon, Dr. M. Nasrul Kamal, M.Sn., Riri Trinanda, S.Pd., M.Sn., (DEKAVE : Jurnal Desain Komunikasi Visual, 2018)
Today's entertainment world has experienced many improvements and is growing rapidly. The presence of entertainment service providers is a solution to meet the need for entertainment. Karaoke is one of the entertainment that is developing in Indonesia. Karaoke in Indonesia began in 1998, and until now the karaoke business has grown and attracted many people, therefore there is a karaoke service provider company that has a good brand quality, so they are the ones who deserve appreciation from consumers.The purpose of this design is a manifestation of the writer's desire to build a new and positive image from Ririez Karaoke. Karaoke place so far has a bad image in society therefore with this design is expected to be able to change the public perception about karaoke place and make Ririez Karaoke has its own image. This design is carried out through several stages, namely data collection, data analysis and design. The process of collecting data through interviews with owner Ririez Karaoke. While the data analysis process with the S W O T method is obtained through the collection of observation and documentation data directly to Ririez Karaoke.The Visual Design of Ririez Branding Karaoke The City of Mukomuko Bengkulu will produce the main media in the form of a Manual book that serves as a guide to applying the brand to be consistent and maintain the character of Ririez Karaoke. This design is also supported by several other media such as: Stationery set, X Banner, Pin, Sticker, Poster, Shirt that acts as the main media support and as a promotional medium.Keyword : Karaoke place, Ririez Karaoke, Manual book, Brand, Image.